Improvement of initial guess via grid‐cutting for efficient grid‐based density functional calculations. Issue 19 (30th June 2016) - Lim, Jaechang; Choi, Sunghwan; Kang, Sungwoo; Kim, Jaewook; Hong, Kwangwoo; Kim, Woo Youn
Abstract: We introduced an efficient initial guess method, namely the grid‐cutting, which is specialized for grid‐based density functional theory (DFT) calculations. It produces initial density and orbitals through pre‐DFT calculations in an inner simulation box made by cutting out the outer region of a full‐size one. To assess its performance, we carried out DFT calculations for small molecules included in the G2‐1 set and two large molecules with various combinations of mixing and diagonalization conditions, relative size of the inner box, and grid spacing. For all cases, the grid‐cutting method was more efficient than conventional ones such as extended Hückel, superposition of atomic densities, and linear combination of atomic orbitals. For instance, it was about 20% faster in computational time and about 45% smaller in the number of self‐consistent‐field cycles than the superposition of atomic densities because it provided high‐quality initial density and orbitals closer to the corresponding fully converged values. In addition, it showed good performance for non‐Coulombic model systems such as harmonic oscillator. Abstract : A novel, efficient initial guess method shows better performance than conventional methods in grid‐based density functional calculations. This approach is able to provide high‐quality initial density and orbitals by performing pre‐DFT calculations in a simulation box obtained by eliminating the outer region of the full model. This method is also effective for non‐Coulombic model systems, such as the harmonic oscillator and quantum wells.